A randomized placebo−controlled clinical trial of oral green tea epigallocatechin 3−gallate on erythropoiesis and oxidative stress in transfusion−dependent β−thalassemia patients - Settakorn, Kornvipa; Hantrakool, Sasinee; Petiwathayakorn, Touchwin; Hutachok, Nuntouchaporn; Tantiworawit, Adisak; Charoenkwan, Pimlak; Chalortham, Nopphadol; Chompupoung, Anchan; Paradee, Narisara; Koonyosying, Pimpisid; Srichairatanakool, Somdet (Frontiers in Molecular Biosciences, 2024)
β-Thalassemia patients suffer from ineffective erythropoiesis and increased red blood cell (RBC) hemolysis. Blood transfusion, erythropoietic enhancement, and antioxidant supplementation can ameliorate chronic anemia. Green tea extract (GTE) is comprised of catechin derivatives, of which epigallocatechin-3-gallate (EGCG) is the most abundant, presenting free-radical scavenging, iron-chelating, and erythropoiesis-protective effects. The present study aimed to evaluate the effects of GTE tablets on the primary outcome of erythropoiesis and oxidative stress parameters in transfusion-dependent -thalassemia (TDT) patients. Twenty-eight TDT patients were randomly divided into placebo and GTE tablet (50 and 100 mg EGCG equivalent) groups and assigned to consume the product once daily for 60 d. Blood was collected for analysis of hematological, biochemical, and oxidative stress parameters. Accordingly, consumption of GTE tablets improved blood hemoglobin levels when compared with the placebo; however, there were more responders to the GTE tablets. Interestingly, amounts of nonheme iron in RBC membranes tended to decrease in both GTE tablet groups when compared with the placebo. Importantly, consumption of GTE tablets lowered plasma levels of erythroferrone (p < 0.05) and reduced bilirubin non-significantly and dose-independently. Thus, GTE tablets could improve RBC hemolysis and modulate erythropoiesis regulators in transfusion-dependent thalassemia patients.